Analisis Pengaruh Nilai Kalor Batubara Dan Excess Air Terhadap Efisiensi Boiler Di Pembangkit Listrik Pltu Moramo - Putra, Bima Rangga; Mangalla, Lukas Kano; Gunawan, Yuspian (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
Boiler is the most important part of a steam power plant. In this analysis, a water pipe tipe boiler is used which is operated at PLTU Moramo. The purpose of this study was to analyze the effect of the calorific value of coal fuel and excess air on the efficiency of a pulverizer coal boiler with a capacity of 230 T/H at PLTU Moramo. The research was carried out by taking parameter data that was read in the PIMS application at DCS, certificates of coal analysis results, and daily reports from the operations division. The data that has been obtained is then used to calculate enthalpy, LHV, efficiency, and excess air. The results show that the efficiency of the calculation on the data obtained, the efficiency of the use of coal shipment 1912028 with an LHV value of 23.916.31 kJ/Kg which has an efficiency of 65.54% higher than coal shipment 2009075 with an LHV value of 23,183.90 kJ/Kg which has an efficiency of 62.98%. At the highest boiler efficiency of 65.54% achieved at 29.07% excess air.Keywords: PLTU, LHV, boiler efficiency, Excess air, Coal heat